Study of elastoplastic deformations during static and dynamic interaction of two deformable solid bodies. Indenter with a conical tip - D. I. Chernyavsky (Омский научный вестник)
The work analyzes the dynamic and static relationships between force and indentation depth when conical indenters are pressed into various materials. The indenter consists of a cylindrical body with a pointed conical tip. Indenters and targets are fabricated from steel, duralumin, and brass. Through digitization of graphs representing the investigated relationships, interpolation formulas describing the distribution of elastic and plastic deformation energies within the contact zone are derived. The obtained results can be applied in the design of dies and matrices for material forming processes, as well as in the determination of parameters for technological operations during the fabrication of profiled parts from steel and duralumin sheets.